The New Politics of Religious Freedom Humanitarian Aid and Sanctuary as Religious Mandates - Alexander, Laura E. (2021)
Interreligious organizations that provide aid to immigrants are changing the way scholars and the public understand religious freedom in the United States. Members of these organizations draw on laws and ideals of free exercise of religion to challenge policies that limit humanitarian aid to immigrants. At the same time, they create networks across religious difference. In so doing, these groups enter a global debate over the value of borders and boundaries, making a religiously grounded case for building bonds of fellowship across both national borders and the boundary lines that separate people based on identity. The work of these groups provides a window both into legal debates over religious freedom, and postcolonial challenges to modern-era categories of difference.